Characterizing the HIV Epidemic in the Prairie Provinces - Marissa L Becker; Ken Kasper; Carla Pindera; Mary Cheang; Debbie Rodger; Stephen Sanche; Stuart Skinner; M John Gill (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The numbers and demographics of HIV-positive patients in care between 2003 and 2007 in the prairie provinces were examined.